Clinical Misdiagnosis of COVID-19 Infection with Confusing Clinical Course. (31st March 2021) - Eshaghi, Hamid; Ziaee, Vahid; Khodabande, Mahmood; Safavi, Moeinadin; Haji Esmaeil Memar, Elmira
Abstract : Background . Similarities in the febrile course and other manifestations of some diseases may lead to clinical misdiagnosis of COVID-19 infection. Here, we report a case in a young child with a potentially confusing clinical course. Case Presentation . A 29-month-old boy presented with a 2-month history of fever. His PCR test for COVID-19 was positive, and there was pleural effusion plus positive findings in the lower left lobe of the lung on computed tomography scan. Mid-sized splenomegaly was found on abdominal ultrasound, and laboratory tests disclosed pancytopenia. In light of the atypical lymphocyte counts in laboratory tests, he underwent bone marrow aspiration. The suggested diagnosis was hemophagocytic lymphohistiocytosis, and prednisolone was initiated. Subsequently, Leishman-Donovan bodies were seen in the bone marrow aspirate, and treatment was started with amphotericin, which led to clinical improvement. Conclusion . In cases with vague clinical symptoms in tropical countries where other infectious diseases occur, possible simultaneous infection should be considered even during a pandemic. Familiarity with the possible differential diagnoses and appropriate, step-by-step consideration to rule out other possible causes are needed in all situations, and the coexistence of infectious disease should be considered in evaluating the clinical conditions of patients in tropical countries.